2017
DOI: 10.1021/acs.langmuir.6b03276
|View full text |Cite
|
Sign up to set email alerts
|

Nanoroughness Strongly Impacts Lipid Mobility in Supported Membranes

Abstract: In vivo lipid membranes interact with rough supramolecular structures such as protein clusters and fibrils. How these features whose size ranges from a few nanometers to a few tens of nanometers impact lipid and protein mobility is still being investigated. Here, we study supported phospholipid bilayers, a unique biomimetic model, deposited on etched surfaces bearing nanometric corrugations. The surface roughness and mean curvature are carefully characterized by AFM imaging using ultrasharp tips. Neutron specu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…There is already substantial evidence of a support's influence on bilayer diffusion [25][26][27][28] . To further assess the influence of support on other pivotal biophysical parameters and the relationships between them, we have selected four models that broadly represent the spectrum of designs extensively utilised.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is already substantial evidence of a support's influence on bilayer diffusion [25][26][27][28] . To further assess the influence of support on other pivotal biophysical parameters and the relationships between them, we have selected four models that broadly represent the spectrum of designs extensively utilised.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid ordering was comparable between GUVs, SLBs, and BSLBs of equal composition -at least at the microscopic scale, suggesting a more direct influence of support on diffusion. Indeed, the drag imparted by a lipid support is widely appreciated 18,27 . However, our application of STED-FCS adds a spatial-temporal framework for these interactions and suggests repeated, but brief interactions between support and constituting lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased roughness has been shown to reduce diffusion up to 5-fold on etched glass and silicon surfaces (Rq=0.1-3 nm) 47 and silicon zerogels (Rq=0.71 nm) 48…”
Section: Lipid Diffusionmentioning
confidence: 99%
“…Then, dynamical aspects of cell adhesion and migration can be studied as the acquisition time is typically few hundreds ms. NEFM is also relevant to study th interaction and diusion of supported lipid bilayers on nanoroughness surfaces. 42 Finally, this method is also well suited to study biological samples as it was previously demonstrated. 19 We believe that our technic can be used to probe the dynamic of focal adhesions and also localize precisely cell integrins involved in the focal adhesion plaques.…”
Section: Resultsmentioning
confidence: 82%